Yog’-moy sanoatida noаn’аnаviy moylаrning аhаmiyаti - Najmitdinova Guljahon Komiljon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
After Uzbekistan gained independence, the monopoly on cotton production was abolished in the republic. Grain and grain crops are sown in cotton fields. As a result, the number of cotton seeds has decreased.